Genomic signatures of pancreatic adenosquamous carcinoma (PASC). Issue 2 (5th September 2017) - Fang, Yuan; Su, Zhe; Xie, Jing; Xue, Ruidong; Ma, Qi; Li, Yanmeng; Zhao, Yifan; Song, Zeshi; Lu, Xiongxiong; Li, Hongwei; Peng, Chenghong; Bai, Fan; et al.
Abstract: In pancreatic cancer, pancreatic adenosquamous carcinoma (PASC) containing both ductal adenocarcinoma and squamous carcinoma in the same tumour represents ∼4% of the total incidence. To date, the genomic features of this mixed tumour are still unknown. We analysed the genomes of 17 PASCs and 34 pancreatic ductal adenocarcinomas (PDACs), and showed that PASC carried highly enriched TP53 mutations and 3p loss as compared with PDAC. We also showed that adenomatous and squamous components of PASC harboured comparable genomic alterations, suggesting that the two cellular components develop from the same progenitor cancer cells. Our study has updated genomic knowledge to help with understanding mixed cancers of the pancreas. Copyright © 2017 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.